2016
DOI: 10.1007/s40268-016-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction of Rifampicin with Oral Versus Intravenous Anticancer Drugs: Challenges, Dilemmas and Paradoxical Effects Due to Multiple Mechanisms

Abstract: Since many drugs are cytochrome P450 (CYP)-3A4 substrates, it has become common practice to assess drug–drug interaction (DDI) potential with a CYP3A4 inhibitor (ketoconazole) or inducer (rifampicin) in early drug development. Such an evaluation is relevant to anticancer drugs with metabolism governed by CYP3A4. DDIs with rifampicin are complex, involving other physiological mechanisms that may impact overall pharmacokinetics. Our objective was to study and delineate such mechanisms for oral versus intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Multiple mechanisms may also characterize potential clinical DDIs between rifampicin and CDK4/6 inhibitors. Rifampin can affect other physiological processes beside CYP3A4, including P-gp [41] and UGT induction [56], that need to be considered as likely perpetrator mechanisms in patients receiving CDK4/6 inhibitors.…”
Section: Complex Ddismentioning
confidence: 99%
“…Multiple mechanisms may also characterize potential clinical DDIs between rifampicin and CDK4/6 inhibitors. Rifampin can affect other physiological processes beside CYP3A4, including P-gp [41] and UGT induction [56], that need to be considered as likely perpetrator mechanisms in patients receiving CDK4/6 inhibitors.…”
Section: Complex Ddismentioning
confidence: 99%
“…While rifampicin has been used extensively as a probe to evaluate CYP3A4 induction in drugdrug interaction studies, definitive attribution of any observed interaction to CYP3A4 induction can be complicated because rifampicin also interacts with a number of other enzymes that may affect the overall PK of coadministered drugs. 18 In addition to the CYP3A4 pathway, rifampicin may also interact with vemurafenib through induction of P-gp and/or other phase 2 conjugation enzymes. In a recent animal study, rifampicin was shown to reduce single-dose vemurafenib plasma exposure through induction of efflux transporters (most likely P-gp) rather than the CYP3A pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating the impact of pregnancy and EFV helps inform specific recommendations for both HIV‐uninfected and EFV‐treated pregnant women and indicates that each factor must be considered separately for other treatment guidelines, for example, for tuberculosis . Metabolic induction of CYP and potentially UGT can be impacted by other intrinsic mechanisms, such as induction of drug transporters including p‐glycoprotein . An interplay of multiple factors may have resulted in the distinct effects of pregnancy and EFV on exposure to DHA and piperaquine.…”
Section: Discussionmentioning
confidence: 99%